Comparative study of capital structure between some selected GLCs and NGLCs in Malaysia (1998 - 2012) / Anita Ariffin - Ariffin, Anita (2014)
This study investigates the comparison of capital structure among publicly listed Government Linked Companies (GLCs) and Non-Government Linked Companies (NGLCs) in Malaysia. A total of 4 companies consist of both two GLCs and NGLCs are analyzed covering the period from 1998 to 2012. This study uses debt ratio as dependent variables and four independent variables that is profitability, liquidity, tangibility and firm's size. Multiple regression analysis and Pearson Correlation was used as a method of analysis. The findings indicate that a significantly positive relationship between debt ratio (DR) and firm's size for GLCs and NGLCs. The result also reveals that profitability, liquidity and tangibility have no influence on the debt ratio (DR) of GLCs and NGLCs. In addition, NGLCs are consistently more heavily levered than GLCs. Generally, both GLCs and NGLCs support trade off theory and pecking order theory.